Eco-Habituation Learning (EHL): Internalizing ESD Values through Habit Formation to Foster Environmentally Friendly Behavior Among Students - Maniah Maniah; Abd. Wafir Ramadhani; Mochamad Arifin Alatas (IAIN Madura, 2026)
This study aims to analyze the application of Eco-Habituation Learning (EHL) in internalizing ESD values to foster environmentally friendly behavior among students. In addition, this study can also provide practical insights into the development of environment-based learning models that are in line with the times and the needs of today’s students. This study employed a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation, which were analyzed thematically. The results indicate that the implementation of EHL through consistent practice, coupled with the supervisory support of teachers and school principals, significantly fosters students’ environmentally conscious attitudes. Such habit formation encourages students to internalize environmental values through direct experience; EHL has proven effective as a learning approach in supporting the implementation of ESD in schools. Therefore, it is recommended that schools integrate habit-forming strategies systematically and continuously to strengthen students’ environmentally conscious character.